Plasma of underwater electric discharges with metal vapors - Boretskij, V.F.; Veklich, A.N.; Tmenova, T.A.; Cressault, Y.; Valensi, F.; Lopatko, K.G.; Aftandilyants, Y.G. (Вопросы атомной науки и техники, 2019)
This paper deals with spectroscopy of underwater electric discharge plasma with. In particular, the focus is on configuration where the electrodes are immersed in liquid and its application in nanoscience and biotechnology. General overview of the experimental approach adopted by authors aiming to study the water-submerged electrical discharge plasma and effects of various parameters on its properties is described. The electron density was estimated on the base of spectral line broadening and shifting.